Rumensin®-Tylan® combinations in limit-fed growing diets: effects on growing and finishing performance and carcass characteristics - Montgomery, Sean P.; Farran, T.B.; Sindt, J.J.; Coetzer, C.M.; Pike, J.N.; Trater, A.M.; LaBrune, H.J.; Hunter, R.D.; Laudert, S.B.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five hundred seventy-two crossbred beef heifers were used to compare gain and feed efficiency of cattle consuming restricted quantities of energy-dense growing diets containing varying concentrations of Rumensin® and Tylan®. Growing treatments consisted of providing Rumensin at 30 grams per ton of dry matter (R30), or 250 mg per head per day (R250). A third treatment consisted of a Rumensin/Tylan combination, providing 250 and 90 mg per head per day of Rumensin and Tylan, respectively (R250/T90). Average daily gain and feed efficiency during the growing phase were not different (P>0.90) among treatments. Heifers that received R250/T90 during the growing phase exhibited lower dry matter intakes (P<0.05) during the finishing phase. Although not significant (P>0.50), R250/T90 increased finishing-phase feed efficiency by 6.1 and 3.5% compared to R30 and R250, respectively. Liver abscesses were lower (P<0.10) for R250/T90 and R30 than R250.
Keywords: Beef; Rumensin; Tylan; Limit feeding